The role of motivation and social network on crowdfunding sites in Indonesia - Anom Purbawangsa, Ida Bagus Panji Sedana, Sayu Ketut Sutrisna Dewi, I Gusti Bagus Wiksuana, Ida Bagus (Opción, 2020)
This study aims to determine the role of motivation and social networking in mediating the influence of collective culture on investment in crowd funding sites in Indonesia. The population is all investors who have invested during 2017-2018 on sites that have been registered and monitored by the Financial Services Authority. The data analysis technique used was SEM PLS and primary data were collected through a questionnaire. Results of the analysis found that collective culture influences motivation, social networking, and investment positively and significantly; social networking significantly influences motivation; there is no influence of social networks on investment.